My blue heaven - Ephron, Nora; Ross, Herbert; Ross, Herbert; Sylbert, Anthea (Warner Home Video, 1990)
Trades the mob for the witness protection program and moves to a small suburb in California. But for Vinnie, old ways die hard. He becomes a challenge for Barney Coopersmith (Rick Moranis), the FBI agent in charge of making sure Vinnie keeps a low profile before he can testify against his former mob associates. Barney, though, might actually be able to learn some things from Vinnie. That is, if Barney can keep him alive long enough.